The Effect of Disciplinary Training and Workload on the Performance of Civil Servants (PNS) in the Assessment and Service Division of the Regional Revenue Agency of XYZ Regency - Nafa Raudatul Jannah; Dian Lestari (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This investigation seeks to determine the impact of disciplinary training also workload on the performance of civil servants (PNS) in the Assessment and Services Division of the Regional Revenue Agency of XYZ Regency, both simultaneously also partially. Multiple linear regression analysis also the coefficient of determination using SPSS 23 were employed in the quantitative investigation technique. Data collection was conducted via questionnaires, interviews, also documentation, involving 34 employees in the Assessment and Services Division and 1 division head of the Assessment and Services Division. The findings of the investigation show disciplinary training has a positive influenceon employee performance, and workload has a positive influenceon on employee performance; simultaneously, disciplinary training also workload together influence employee performance. This suggests that the better the disciplinary training and workload management, the more optimal the employees’ performance will be.